Core and bridge symptoms of demoralization in Chinese female cancer patients: a network analysis - Gong, Yijing; Shang, Bin; Tan, Jianing; Luo, Caifeng; Bian, Zekun; Wu, Xiaoxiang; Fan, Tingting; Zhao, Qian; Liu, Lili; Sun, Weiyi (Frontiers in Psychiatry, 2024)
Objective In this study, we explore the core and bridge symptoms of demoralization in female cancer patients in China, and provide a basis for precise psychological intervention among female cancer patients. Methods This study used a cross-sectional survey. Participants were recruited from three third-class hospitals in Jiangsu Province from June 2022 to June 2023 using the convenience sampling method. The severity of each symptom of demoralization was investigated in female cancer patients using the Demoralization Scale (DS). Network analysis was performed using the R language to identify core and bridge symptoms in the network and further explore some characteristic edge connections in the network. Results The network structure model of demoralization had strong accuracy and stability. In the network, the symptoms with the highest strength centrality were “Discouragement” (C3, strength=2.19), “No self-worth” (A3, strength=1.21), “Don’t want to live” (A5, strength=1.20), “Hopeless” (D4, strength=0.81), and “Vulnerability” (B3, strength=0.74), respectively. The bridge strength analysis identified “Hopeless” (D4, bridge strength=0.92), “Discouragement” (C3, bridge strength=0.85), “No self-worth” (A3, bridge strength=0.75), “Poor spirits” (E2, bridge strength=0.71), and “Vulnerability” (B3, bridge strength=0.69) as the bridge symptoms. The strongest edge connections of all dimensions were “No self-worth” and “Worthless” (A3—E6, edge weighting=0.27), “Poor spirits” and “Loss of emotional control” (E2—D1, edge weighting=0.22), “Discouragement” and “Vulnerability” (C3—B3, edge weighting=0.14), and “Hopeless” and “No meaning of survival” (D4—A4, edge weighting=0.12). Conclusion “Discouragement (C3)”, “No self-worth (A3)”, “Hopeless (D4)”, and “Vulnerability (B3)” are both core symptoms and bridge symptoms. These symptoms can not only trigger a patient’s demoralization but also stimulate more severe symptom clusters through interactions. The early recognition of and intervention regarding these symptoms could be important for the prevention and treatment of demoralization among female cancer patients.